The Role of School Committees and Associations in Supporting Competitive Advantage in Muhammadiyah Elementary School 2 Krian: Peran Komite Sekolah dan Paguyuban dalam Mendukung Keunggulan Bersaing di Sekolah Dasar Muhammadiyah 2 Krian - Fahrur, Amam; Haryanto, Budi (Journal of Islamic and Muhammadiyah Studies, 2023)
This research is a case study research because the focus of this research is to answer the question "how" the role of class committees and associations at SD Muhammadiyah 2 Krian, and wants to cover contextual conditions that are relevant to the phenomenon. This research was conducted at SD Muhammadiyah 2 Krian, Sidoarjo. The results of this study indicate that the school committee has helped competitive advantage in SD Muhammadiyah 2 Krian in terms of low cost (low cost), and differentiation, but the committee has not been able to increase competitive advantage in terms of focus. In terms of low cost, the committee through the education sector has formed GK-OTA (Foster Parents Committee Movement) which provides scholarships to underprivileged students and helps with education costs for students who need tuition assistance. In terms of differentiation, the committee through the economic sie. In addition to the committee, the association has also shown its role in creating good relationships between fellow guardians of students, this provides benefits for schools in establishing communication, be it institutional communication, or cultural communication.